2021
DOI: 10.1080/1461670x.2021.1932560
|View full text |Cite
|
Sign up to set email alerts
|

From “Far Away” to “Shock” to “Fatigue” to “Back to Normal”: How Young People Experienced News During the First Wave of the COVID-19 Pandemic

Abstract: This paper explores how young people used and experienced news during the first wave of the COVID-19 pandemic. Drawing from 22 in-depth interviews with Dutch young people (19-36), we found four successive phases in which participants used and made sense of news in distinct ways. First, before the virus reached the Netherlands, they saw it as "a problem far away" and felt indifferent toward the news. During the second phase of "shock", as COVID-19 reached the Netherlands, news use increased as participants fran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 27 publications
2
31
0
Order By: Relevance
“…Now isolated, participants reported an intensification of news practices at the onset of the national lockdown. Here, we find a reflection of patterns described by previous authors related to both information seeking behaviour (Albertson and Gadarian 2015) as well as the coronavirus pandemic (Ohme et al 2020;Groot Kormelink and Klein Gunnewiek 2021) where users specifically seek out information to cope with "insecurities", and turn to messaging apps to discuss the information they found among peers: "When the first measures were announced, we immediately started sharing and discussing them. It was on everyone's minds" (Jessica, 27, F).…”
Section: The Changing News Environment Of the Pandemicsupporting
confidence: 67%
See 1 more Smart Citation
“…Now isolated, participants reported an intensification of news practices at the onset of the national lockdown. Here, we find a reflection of patterns described by previous authors related to both information seeking behaviour (Albertson and Gadarian 2015) as well as the coronavirus pandemic (Ohme et al 2020;Groot Kormelink and Klein Gunnewiek 2021) where users specifically seek out information to cope with "insecurities", and turn to messaging apps to discuss the information they found among peers: "When the first measures were announced, we immediately started sharing and discussing them. It was on everyone's minds" (Jessica, 27, F).…”
Section: The Changing News Environment Of the Pandemicsupporting
confidence: 67%
“…In the wake of the pandemic, audiences appeared to increasingly seek out news in order to stay informed. Recent studies have shown an increase in news consumption in Flanders (Anrys et al 2020;Ohme et al 2020;Vandendriessche et al 2021), a trend which had also been noticed globally since the start of the pandemic (Nielsen 2020;Groot Kormelink and Klein Gunnewiek 2021). These findings resonate with research which argued that times of crisis, and feelings of anxiety, can form significant motivators in increasing information seeking behaviour in users (Albertson and Gadarian 2015;Westlund and Ghersetti 2015).…”
Section: Introductionmentioning
confidence: 64%
“…This bedtime news engagement may, then again, further foster people's COVID-19 information FOMO, and the loop starts anew. People who are stuck in this reinforcing spiral may be less likely to engage in efficient coping behaviors, such as selective news engagement ( Ahmed, 2020 ; Groot Kormelink & Klein Gunnewiek, 2021 ), to avoid more severe consequences and may be more likely to become “news junkies” for whom news engagement is compulsive ( Broersma & Swart, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The pandemic "has substantially increased news consumption for mainstream media" as is shown in a survey conducted in 2020 in the U.K., the U.S., Germany, Spain, South Korea and Argentina [2]. People search more intensively for information to make sense of a new, disruptive situation like a crisis [3]. As agenda-setters, journalists fuel and respond to these information needs [4].…”
Section: Introductionmentioning
confidence: 99%
“…As agenda-setters, journalists fuel and respond to these information needs [4]. But in the case of COVID-19, news media's herd behavior cascaded in overreporting on the topic, such that the longer the pandemic lasted, the more people became "coronavirus-news-fatigued" [3,5]. Decisionmakers in organizations engage in issue management to cope with exogenous challenges such as those posed by the pandemic crisis.…”
Section: Introductionmentioning
confidence: 99%